Prevalence of Positive Troponin and Echocardiogram Findings and Association With Mortality in Acute Ischemic Stroke. Issue 5 (May 2017) - Wrigley, Peter; Khoury, Jane; Eckerle, Bryan; Alwell, Kathleen; Moomaw, Charles J.; Woo, Daniel; Flaherty, Mathew L.; De Los Rios la Rosa, Felipe; Mackey, Jason; Adeoye, Opeolu; Martini, Sharyl; Ferioli, Simona; et al.
Abstract : Background and Purpose—: Acute ischemic stroke (AIS) patients may have raised serum cardiac troponin levels on admission, although it is unclear what prognostic implications this has, and whether elevated levels are associated with cardiac causes of stroke or structural cardiac disease as seen on echocardiogram. We investigated the positivity of cardiac troponin and echocardiogram testing within a large biracial AIS population and any association with poststroke mortality. Methods—: Within a catchment area of 1.3 million, we screened emergency department admissions from 2010 using International Classification of Diseases, Ninth Edition, discharge codes 430 to 436 and ascertained all physician-confirmed AIS cases by retrospective chart review. Hypertroponinemia was defined as elevation in cardiac troponin above the standard 99th percentile. Multiple logistic regression was performed, controlling for stroke severity, history of cardiac disease, and all other stroke risk factors. Results—: Of 1999 AIS cases, 1706 (85.3%) had a cardiac troponin drawn and 1590 (79.5%) had echocardiograms. Hypertroponinemia occurred in 353 of 1706 (20.7%) and 160 of 1590 (10.1%) had echocardiogram findings of interest. Among 1377 who had both tests performed, hypertroponinemia was independently associated with echocardiogram findings (odds ratio, 2.9; 95% confidence interval, 2–4.2). When concurrent myocardial infarctions (3.5%) were excluded, hypertroponinemia was also associated with increased mortality at 1 year (35%; odds ratio, 3.45; 95% confidence interval, 2.1–5.6) and 3 years (60%; odds ratio, 2.91; 95% confidence interval, 2.06–4.11). Conclusions—: Hypertroponinemia in the context of AIS without concurrent myocardial infarction was associated with structural cardiac disease and long-term mortality. Prospective studies are needed to determine whether further cardiac evaluation might improve the long-term mortality rates seen in this group. Abstract : Supplemental Digital Content is available in the text.